2002
DOI: 10.1053/rmed.2002.1392
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the burden of respiratory disease in the UK

Abstract: This review explores the health and social burden of some of the main respiratory diseases (asthma, chronic obstructive pulmonary disease, cryptogenic fibrosing alveolitis, cystic fibrosis, lung cancer, mesothelioma, obstructive sleep apnoea and tuberculosis) in order to increase awareness of these diseases and highlight areas where improvements in care are required. The overall impact of respiratory diseases in the U.K. in terms of prevalence, mortality, morbidity and economic costs, with particular reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 49 publications
1
34
0
1
Order By: Relevance
“…1 It is rarely observed as an isolated pathology, often being associated with asthma, [2][3][4][5] sinusitis, lymphoid tissue hypertrophy and obstructive sleep apnea. [2][3] There is a prevalence of 75 to 80% of asthma in patients who have allergic rhinitis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 It is rarely observed as an isolated pathology, often being associated with asthma, [2][3][4][5] sinusitis, lymphoid tissue hypertrophy and obstructive sleep apnea. [2][3] There is a prevalence of 75 to 80% of asthma in patients who have allergic rhinitis.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3] There is a prevalence of 75 to 80% of asthma in patients who have allergic rhinitis. 5 Many of these patients also display mouth breathing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Ventilatory failure is defined as the inability of the respiratory system to function effectively as a pump, resulting in hypoxaemia (PaO 2 <8.9 kpa/60 mmHg) and hypercapnia (PaCO 2 >6.7 kpa/50 mmHg). The hallmark of life-threatening ventilatory failure in the decompensated form is characterised by the presence of respiratory acidosis when arterial pH falls below 7.35 in addition to the gas exchange abnormalities mentioned above.…”
mentioning
confidence: 99%
“…R espiratory diseases are responsible for a significant proportion of serious morbidity and premature death. Recent reports from the United Kingdom showed that respiratory diseases accounted for 6.5% of hospital admissions and 24% of all deaths (1). An American survey on the use of physician offices by adolescents showed that for the age groups 11 to 14 years and 18 to 21 years, the leading reason for visits were respiratory disorders (19.4% and 11.3%, respectively) (2).…”
mentioning
confidence: 99%